PAT MORA’S SELF-CONCEPT OF BEING A MEXICAN-AMERICAN IN LEGAL ALIEN - RAHMAWATI, ATIKA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: self-concept, social experiences, Mexican-American, Legal AlienMexican-American is racial minority in the United States. Negative stereotypes about them being illegal immigrant, low rank worker, and having bad attitudes are believed to be true by many. It is affecting the way MexicanAmericans view themselves and how they act in the society. A poem entitled Legal Alien is interesting in showing the development of how someone with Mexican-American identity realizes her place in society.This research is conducted to analyze the realization of self-concept of Mexican Americans and what are the factors that influence it, with Pat Mora as the representative. Social psychological approach is utilized in this research in order to explain the social experiences that determine one’s self-concept. This research also applies a qualitative approach through document analysis to examine the data taken from the poem.The poem implies the situation and condition that are Mexican-Americans facing. They are being rejected by both American and Mexican cultures. The findings of this research shows that out of five social experiences that influences the realization of self-concept, the other people’s judgment and the surrounding culture are the most dominant factor in shaping Pat Mora’s concept about herself.This research concludes that Pat Mora as the author has a purpose to gain attention from people in her surrounding to treat Mexican-Americans appropriately. No one wanted to be alienated from the society, so do the Mexican Americans.